Substance Abuse Risk and Medication Monitoring in Patients with Advanced Lung Cancer Receiving Palliative Care. (3rd April 2021) - Kumar, Pooja S.; Saphire, Maureen L.; Grogan, Madison; Benedict, Jason; Janse, Sarah; Agne, Julia L.; Bertino, Erin M.; Presley, Carolyn J.
Abstract: Oncology and Palliative Medicine lack guidance on routine opioid risk screening and compliance monitoring. This study explored relationships among risk screening and aberrant medication related behaviors in patients with advanced lung cancer receiving embedded palliative care. This was a single center, prospective study and data was collected from December 2018 to March 2020. At the initial palliative visit, patients provided a baseline urine drug screen (UDS) test and completed the Screener and Opioid Assessment for Patients with Pain – Revised (SOAPP-R) self-assessment. Clinical pharmacists provided comprehensive review and interpretation of UDS results. Among 39 patients, 12 (30.8%) scored positive for risk of aberrant medication behaviors on the SOAPP-R. Only 34 of 39 patients provided a baseline UDS test and were included in further analysis. Prior to pharmacist review, 11/11 (100%) baseline UDS results in the positive-risk group and 13/23 (56.5%) in the negative-risk group appeared unexpected ( p  = 0.01). After pharmacist review, aberrant baseline UDS results were confirmed for 5/11 (45.5%) positive-risk and 4/23 (17.4%) negative-risk patients ( p  = 0.11). Overall, the SOAPP-R alone may be inadequate in this population and clinical pharmacists play an important role in comprehensive UDS result interpretation. Future studies are needed to validate this risk-screening tool in palliative cancer populations.